Special Olympics - Brown, Fern G. (New York : F. Watts, 1992)
Describes the history and organization of the Special Olympics and explains how athletes and volunteers can get involved.
Includes index.
Elem. School Library Collection.
School Library Journal.
Wilson's Junior High School.
6.5
4-6